PRODUKTIVITAS SERASAH MANGROVE DI PERAIRAN KAWAL KABUPATEN BINTAN - Anggriani, Anggriani; Azizah, Diana; Kurniawan, Dedy (Biospecies, 2025)
Research on the productivity of mangrove litter in the Kawal Waters of Bintan Regency. The purpose of this study is to determine the production and decomposition rate of mangrove litter as well as the relationship between mangrove conditions and litter production in the Kawal Waters of Bintan Regency. This research was conducted in July - August 2024. The method used was direct field survey. The location determination method used random sampling of 20 points scattered in the Kawal Waters. The litter sampling method used traps with litter traps measuring 1 m × 1 m, with 3 placed diagonally. Measurement of canopy cover density and mangrove litter was conducted using plots measuring 10 m × 10 m. The types of mangroves found in Kawal Waters are 9 species, namely Rhizophora stylosa, Rhizophora apiculata, Rhizophora mucronata, Bruguiera cylindrica, Bruguiera gymnorrhiza, Scyphiphora hydrophylacea, Lumnitzera littorea, Xylocarpus granatum, and Sonneratia alba. From 20 research points, a density value ranging from 1000 ind/ha to 4700 ind/ha was obtained, with an average of 2980 ind/ha. The canopy cover at the research locations ranged from 46.45% to 87.85%, with an average of 66.73%. Based on Kepmen LH No. 201 of 2004, the density in Kawal Waters is classified as moderate to good, while the canopy cover is classified as sparse to good. The rate of mangrove litter production at 20 research points has an average of 12.83 g/m²/day, with leaf production at 9.15 g/m²/day, twig production at 0.28 g/m²/day, and fruit/flower production at 3.40 g/m²/day. The decomposition of litter obtained a value of 26% for the average of all sampling points. The results of the regression analysis to determine the relationship between mangrove conditions, namely density and percentage cover, and litter production obtained an R value of 0.953, which has a very strong correlation coefficient relationship.